2010
DOI: 10.1136/adc.2008.148205
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after neonatal hypoxic-ischaemic encephalopathy

Abstract: Outcome of full-term infants with neonatal encephalopathy of hypoxic-ischemic origin is often assessed in infancy or early childhood and data on outcome in childhood and adolescence is limited. MRI performed in the neonatal period has made a huge contribution to recognition of different patterns of injury. These different patterns of injury are related to the severity of later motor and cognitive disabilities.Long-term follow-up shows that cognitive and memory diffi culties may follow even in children without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
141
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(157 citation statements)
references
References 52 publications
(52 reference statements)
11
141
0
5
Order By: Relevance
“…Our findings are in line with previous studies demonstrating that the outcome after HIE is not limited to CP and/or severe cognitive impairment, but can be associated with cognitive deficits (3, 4, 23) as well as with impaired motor skills in the absence of CP. (3,7,24) Robertson et al were the first to examine school-age neurodevelopmental outcome in children after HIE. They found that non-disabled survivors after moderate HIE showed marked delays in reading, spelling and arithmetic and were more likely to be at least one grade behind controls or those with mild HIE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are in line with previous studies demonstrating that the outcome after HIE is not limited to CP and/or severe cognitive impairment, but can be associated with cognitive deficits (3, 4, 23) as well as with impaired motor skills in the absence of CP. (3,7,24) Robertson et al were the first to examine school-age neurodevelopmental outcome in children after HIE. They found that non-disabled survivors after moderate HIE showed marked delays in reading, spelling and arithmetic and were more likely to be at least one grade behind controls or those with mild HIE.…”
Section: Discussionmentioning
confidence: 99%
“…The basalganglia/thalamus pattern has been associated with severely impaired motor and cognitive outcomes (2, 7) and the watershed-predominant pattern with cognitive impairments that often occur in the absence of functional motor deficits. (2,3) More recently, a correlation of watershedpredominant pattern of injury with verbal IQ has been demonstrated for children at the age of four years. (13) Little is known on the association between neonatal MRI injury pattern and longterm neurodevelopmental outcome in children without major disability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors are currently being investigated for making HIE prognosis: clinical examination, CNS imaging and amplitude EEG (aEEG) (ref. [6][7][8] ). 1.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews have shown that the majority of variables used to predict outcome are limited in their accuracy (5,6). Increasingly, MRI is used to assess the severity in newborns suffering many types of injuries, including hypoxia-ischemia.…”
mentioning
confidence: 99%